LIQUID-LIQUID EXTRACTION AND SPECTROPHOTOMETRIC CHARACTERIZATION OF SOME NEW TERNARY IONASSOCIATION COMPLEXES OF COBALT (II) AND NICKEL (II) - Zalov, Ali Z.; Gasimova, Yavar C.; Ibrahimova, Shala A. (IJRDO-Journal of Applied Science, 2016)
Complex formation and liquid-liquid extraction were studied in systems containing M(II) (M = cobalt or nickel), 2-hydroxy-5-iodothiophenol (HITP), hydrophobic amines (Am), water and chloroform. Two different Am were used: diphenylguanidine (DPG) and triphenylguanidine (TPG).The optimum conditions for extraction of Co(II) and Ni(II) as ternary complexes with the general formula [M(HITP)2](AmH+ )2 were found: pH, shaking time, concentration of HITP and concentration of Am. Some key constants (constants of extraction – Kex, constants of association – β, constants of distribution – KD) and analytical characteristics (molar absorptivities – εmax, Sandell’s sensitivities – SS, limits of detection – LOD, limits of quantification – LOQ, etc.) were determined.